THE RELATIONAL SEMANTICS OF NAFAṠA IN THE QUR’AN: A STUDY IN LIGHT OF TOSHIHIKO IZUTSU’S CONCEPTUAL FRAMEWORK: SEMANTIK RELASIONAL KATA NAFAṠA DALAM AL-QUR’AN: STUDI DALAM PERSPEKTIF KONSEPTUAL TOSHIHIKO IZUTSU - Wibowo, Teguh Hadi; Mulyono, Khubby; Zahro, Mar’atul Azizah; Hidayatullah, Ahmad Syauqi (Journal of Arabic Language and Literature (ALLAIS), 2025)
This study investigates the relational semantics of the word nafaṡa as found in QS. al-Falaq: 4, using Toshihiko Izutsu’s semantic theory to uncover the conceptual and ideological framework embedded in Qur’anic discourse. Through a qualitative-descriptive method and close textual analysis, the research explores the lexical, syntactic, and contextual dimensions of nafaṡa, highlighting its function as more than a physical act of ‘blowing.’ The analysis reveals that nafaṡa serves as a semantic node within a network of oppositional concepts—namely al-syarr (evil), al-‘uqad (knots, internal constraints), and al-taḥṣīn (divine safeguarding)—forming part of the Qur’an’s spiritual cosmology. Far from being merely a linguistic unit, nafaṡa symbolizes a latent metaphysical threat that operates within the Qur’anic worldview and necessitates divine protection. The study contributes to Qur’anic linguistic scholarship by demonstrating how a single lexical item can encode complex ethical, psychological, and theological meanings when analyzed through relational semantics.